When children's testimonies are used as evidence: how children's accounts may impact child custodial decisions. Issue 4 (2nd October 2018) - Otgaar, Henry; Howe, Mark L.
Abstract: In child custody cases, children oftentimes provide allegations of experienced trauma against one of their parents. Such allegations can happen before any investigative interviews (e.g., by the police or child protective services) have taken place. A central theme here concerns how to appraise such allegations and make certain that children's accounts are taken seriously. In the current special issue, the focus is on new work on the functioning of children's memory and its relation to trauma or work on children's suggestibility and memory when they are traumatized. Specifically, key experts in the field of children's memory provided contributions on: (1) the impact of interviewer support and rapport building on children's testimonies, (2) the role of parental alienation in children's testimonial accuracy, and (3) different types of false memories in children's memory reports.